Long‐term effect of exemestane therapy on bone mineral density supported by bisphosphonates: Results of 5‐year adjuvant treatment in postmenopausal women with early‐stage breast cancer. Issue 5 (22nd June 2018) - Hirano, Akira; Inoue, Hiroaki; Ogura, Kaoru; Hattori, Akinori; Yukawa, Hiroko; Sakaguchi, Shiho; Matsuoka, Aya; Tanaka, Natsuko; Kodera, Asaka; Kamimura, Mari; Naritaka, Yoshihiko; Shimizu, Tadao
Abstract: Purpose: Unlike anastrozole, the effect of long‐term exemestane (EXE) therapy on bone mineral density (BMD) is still unknown. We assessed changes in BMD from baseline to 5 years of EXE treatment. Methods: Postmenopausal women with endocrine‐responsive breast cancer receiving EXE as adjuvant therapy were enrolled in this study. EXE was administered for 5 years. The BMD of the lumbar spine (LS) and femoral neck (FN) was assessed by dual‐energy X‐ray absorptiometry at baseline and after 6 months and 1, 2, 3, 4, 5 and 6 years. Oral bisphosphonate (Bis) treatment was initiated when patients were diagnosed with osteoporosis with a T‐score of −2.5 or lower. Results: Eighty‐one patients were enrolled in the study between 2005 and 2010. The median follow‐up period was 54.9 months. Forty‐two patients were administered Bis. Overall, the BMD of the LS increased by 7.3% from baseline and that of the FN increased by 3.4% with 5 years of EXE treatment. At the sixth year (i.e. 1 year after the treatment), BMD of the LS increased by 7.2% and that of the FN increased by 5.7%. Furthermore, the BMD of the FN increased by 12.0% in patients treated upfront with Bis and by 1.2% in those not treated with Bis ( P = 0.0262). Fractures developed in nine patients (11.1%) and seven (8.6%) had fragility fractures. Conclusion: Oral Bis improves BMD of the FN in patients with osteoporosis. Five‐year EXE treatment with proper addition of Bis helps maintain the BMD of the LS and FN at the sixth year.